Hodnocení finanční situace podniku a návrhy na její zlepšení - Machát, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Tato diplomová práce hodnotí finanční situaci podniku společnosti ABC v období let 2005 – 2008 pomocí vybraných metod finanční analýzy. Zjišťuje problémy a navrhuje možná opatření, jež povedou v budoucnu ke zlepšení stávající finanční situace podniku.

This diploma thesis deals with the financial situation of the company ABC within the years 2005 – 2008 on the basis of selected methods of the financial analysis. It determines problems and proposes possible solutions which should result in the improvement of the financial situation of the firm in the following years.
Evaluation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: Finanční situace; finanční analýza; finanční výkazy; SWOT analýza; ziskovost; likvidita; aktivita; zadluženost; Financial situation; financial analysis; financial statements; SWOT analysis; profitability; liquidity; activity; indebtedness